2005
DOI: 10.1007/s10666-005-3334-4
|View full text |Cite
|
Sign up to set email alerts
|

Modeling trihalomethane formation for Jabal Amman water supply in Jordan

Abstract: A mathematical model that expresses Total trihalomethane (TTHM) concentration in terms of initial chlorine concentration, total organic carbon, bromide ion concentration, contact time, and pH is developed for Zai water treatment plant which supplies water to Jabal Amman. The developed mathematical model is for constant temperature of 20 • C. To adjust model calculated TTHM concentrations for temperatures other than 20 • C, another mathematical model that expresses TTHM growth rate as function of temperature is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…In the recent years much attention has been paid to develop predictive models in order to determine the production and the kinetics of DBP formation [19][20][21]. It is reported that the chlorination serves as oxidant in addition to kill the pathogens.…”
Section: Predictive Modelsmentioning
confidence: 99%
“…In the recent years much attention has been paid to develop predictive models in order to determine the production and the kinetics of DBP formation [19][20][21]. It is reported that the chlorination serves as oxidant in addition to kill the pathogens.…”
Section: Predictive Modelsmentioning
confidence: 99%
“…Since the different THM species have been first identified in chlorinated drinking water, many mathematical models have been developed worldwide to predict their concentrations and/or their formation potential for the ultimate objective of understanding their formation mechanisms and controlling their levels in chlorinated drinking water . Chowdhury et al , in a recent review article, mentioned that 118 different mathematical models that predict the concentrations of the different DBPs in finished drinking water are reported in 48 scientific publications.…”
Section: Formation Of the Different Thm Species In Finished Drinking mentioning
confidence: 99%
“…Bromide was determined by the phenol red colorimetric method (American Public Health Association et al 1998b). Total HM content (THM) was estimated according to the methods of Al-Omari et al (2004) and Elshorbagy and Abdulkarim (2006 [Zn]) in water and sediment were determined by acid digestion followed by flame atomic absorption spectrometry using the direct air-acetylene flame method (American Public Health Association et al 1998c) in a GBC 932 Plus spectrophotometer. Arsenic was evaluated by electrothermal atomic absorption spectrometry (American Public Health Association et al 1998d) in a GBC GF3000 graphite furnace system coupled to the spectrophotometer.…”
Section: Study Site and Physicochemical Analysesmentioning
confidence: 99%